PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA MENJUAL DOKUMEN PALSU MELALUI MEDIA SOSIAL FACEBOOK - Ni Nyoman Muryatini (Faculty of Law, Mahasaraswati University, Denpasar, 2020)
The use of information technology today has caused the world to become borderless. Information is spreading quickly and broader. This is used by some individuals to carry out acts against the law by selling fake documents through facebook social media. The research method is a normative legal research aimed at finding and formulating legal arguments, through analysis of the main problems. The technique of collecting legal material is done by studying literature. The approach used in this study is the statutory approach, namely by examining the applicable legal rules related to criminal liability perpetrators of criminal acts selling fake documents through social media facebook.